2019
DOI: 10.1002/ps.5483
|View full text |Cite
|
Sign up to set email alerts
|

Neurotoxicity and mode of action of fluralaner on honeybee Apis mellifera L.

Abstract: BACKGROUND: Fluralaner, a novel pesticide that targets the -aminobutyric acid (GABA) receptor (GABAR) subunit of resistant to dieldrin (RDL), exhibits strong potential to be an insecticide to control agricultural insect pests. However, the risk and action of fluralaner to economic insects, e.g., honeybee Apis mellifera Linnaeus, remains unclear. RESULTS:In this study, both oral and contact toxicity of fluralaner to honeybee were found to be 0.13 g adult -1 . Abamectin, dieldrin, ethiprole, -endosulfan, fiproni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 39 publications
4
22
0
Order By: Relevance
“…(2019), who found that introducing the A2′S mutation into Px RDL1 of susceptible P. xylostella only caused an approximately 3‐fold increase in fipronil resistance. Molecular docking analyses demonstrated that the 6′ amino acid residue is critical for the combination of insect RDL receptors and insecticides, such as fipronil, ethiprole, and dieldrin (Zheng et al ., 2014; Sheng et al ., 2019). The T6′L mutation in Rhipicephalus microplus RDL was detected in fipronil‐ and dieldrin‐resistant strains (Hope et al ., 2010; Janer et al ., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…(2019), who found that introducing the A2′S mutation into Px RDL1 of susceptible P. xylostella only caused an approximately 3‐fold increase in fipronil resistance. Molecular docking analyses demonstrated that the 6′ amino acid residue is critical for the combination of insect RDL receptors and insecticides, such as fipronil, ethiprole, and dieldrin (Zheng et al ., 2014; Sheng et al ., 2019). The T6′L mutation in Rhipicephalus microplus RDL was detected in fipronil‐ and dieldrin‐resistant strains (Hope et al ., 2010; Janer et al ., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Fluralaner (≥95%) was purified from BRAVECTO ® Chew tablet (Merck & Co., Inc., Isando, South Africa) and verified as previously described (Sheng et al ., 2017; Sheng et al ., 2019). GABA and ethiprole (>98%) were purchased from J & K Scientific Ltd. (Beijing, China).…”
Section: Methodsmentioning
confidence: 99%
“…[101] In molecular modelling of RDL subunits from different species (including Apis mellifera) fipronil is erected in the channel pore surrounded by the five M2 segments, the trifluoromethyl group being oriented toward the intracellular compartment. [75,102,103] The binding site of fipronil is located between L9' (which defines the narrowest point of the pore) and P-2', with A2' and T6' critically involved in direct interaction with phenylpyrazole. [75] Lack of conservation of these two residues probably explains the weaker sensitivity of mammalian GABA A for fipronil compared to insect RDL.…”
Section: Insecticide Resistance and Docking In Ligand-gated Chloride ...mentioning
confidence: 99%
“…[75,102,103] The binding site of fipronil is located between L9' (which defines the narrowest point of the pore) and P-2', with A2' and T6' critically involved in direct interaction with phenylpyrazole. [75] Lack of conservation of these two residues probably explains the weaker sensitivity of mammalian GABA A for fipronil compared to insect RDL. [104] Meta-diamides are similarly efficient on a Drosophila melanogaster RDL mutant harboring substitutions at both A2' and T6' than on wild type receptor.…”
Section: Insecticide Resistance and Docking In Ligand-gated Chloride ...mentioning
confidence: 99%